Educational Intervention on Health Related Lifestyle Changes Among Iranian Adolescents - Mohsen Saffari; Najmemolouk Amini; Hasan Eftekhar Ardebili; Hormoz Sanaeinasab; Mahmoud Mahmoudi; Crystal N Piper (Tehran University of Medical Sciences, 2013)
Background: Healthy lifestyle habits during adolescence can prevent many of the diseases and disabilities in adulthood and later. The aim of the study was to examine the role of education in improving lifestyles among Iranian adolescents.Methods: This group randomized controlled trial was conducted during October 2010 until January 2011 in Tehran. Participants for this study were selected through a random sampling method and divided into intervention and control groups. The intervention group received a six session course on healthy lifestyles and the control group received no intervention. The Adolescent Lifestyle Questionnaire (ALQ) was used for collecting data. Data were collected before the intervention, at a two week after participation time point, and a three month follow-up was conducted.Results: Overall, 365 (male: 173, female: 192) adolescents participated in the study. There were significant differences between boys and girls in terms of physical activity and social support (P<0.001). The boys had higher levels of physical activity than girls. Girls received more social support than boys. There were significant differences in the lifestyle scores between the intervention and control groups at follow-up (P<0.001). The educational intervention indicated an improved total lifestyle score (from 123.7(SD.16.1) at baseline to 131.8 (SD.16.7) at two weeks and to 130.5(16.5) at 3 months after education) among the intervention group.Conclusions: Adolescents` behaviors may be different in some dimensions among boys and girls. Unhealthy lifestyle habits are prevalent among adolescents. Therefore sex-specified lifestyle education can bring promising results. Further research in the field can reveal the importance of lifestyle intervention programs.